Pengaruh Profitabilitas, Kebijakan Dividen, Pertumbuhan Perusahaan, Dan Size Perusahaan Terhadap Nilai Perusahaan - Rayhani Risma Utami; Winda Juliana Nababan; Vanji Anesa Siregar; Nur Indah Gulo; Udurrut Sadaria Siahaan (Universitas Muhammadiyah Sorong, 2019)
The purpose of this research to analyze the effect of profitability, dividend policy,growth and firm size to firm value. This research used all the companies listed on Indonesian Exchange in the periods are five which is started from 2013 until 2017. The number of all companies that were became in this study were 36 companies with 5 years observation. Based on method purposive sampling, research sample total is 180 financial statement .The analysis method by using multiple linear regressions. Result of this research indicates that profitability, dividen policy, growth, does not influences significantly positive on the firm value. Meanwhile, firm size influences significantly positive to the firm value.